Novel lawsone-containing ruthenium(II) complexes: Synthesis, characterization and anticancer activity on 2D and 3D spheroid models of prostate cancer cells - De Grandis, Rone Aparecido [UNESP]; Silva dos Santos, Patrick Wellington da; Oliveira, Katia Mara de; Tomazela Machado, Ana Rita; Aissa, Alexandre Ferro; Batista, Alzir Azevedo; Greggi Antunes, Lusania Maria; Pavan, Fernando Rogerio [UNESP] (Elsevier B.V., 2019)
This study describes a series of newly synthesized phosphine/diimine ruthenium complexes containing the lawsone as bioligand with enhanced cytotoxicity against different cancer cells, and apoptosis induction in prostatic cancer cells DU-145. The complexes [Ru(law)(N-N)(2)]PF6 where N-N is 2,2'-bipyridine (1) or 1,10-phenanthroline (2) and [Ru(law)(dppm)(N-N)]PF6, where dppm means bis(diphenylphosphino)methane, N-N is 2,2'-bipyridine (3) or 1,10-phenanthroline (4), and law is lawsone, were synthesized and fully characterized by elemental analysis, molar conductivity, NMR, UV-vis, IR spectroscopies and cyclic voltammetry. The interaction of the complexes (1-4) with DNA was evaluated by circular dichroism, gel electrophoresis, and fluorescence, and the complexes presented interactions by the minor grooves DNA. The phosphinic series of complexes exhibited a remarkably broad spectrum of anticancer activity with approximately 34-fold higher than cisplatin and 5-fold higher than doxorubicin, inhibiting the growth of 3D tumor spheroids and the ability to retain the colony survival of DU-145 cells. Also, the complex (4) inhibits DU-145 cell adhesion and migration potential indicating antimetastatic properties. The mechanism of its anticancer activity was found to be related to increased reactive oxygen species (ROS) generation, increased the BAX/BCL-2 ratio and subsequent apoptosis induction. Overall, these findings suggested that the complex (4) could be a promising candidate for further evaluation as a chemotherapeutic agent in the prostate cancer treatment.
Keywords: Cancer; 1,4-naphthoquinone; 3D-cell culture; ROS; Apoptosis; BAX/BCL-2